Competitive aptamer switch for modulating ligand binding affinity - Derek Puyat; Sung Won Oh; Shiming Liu; Jinglin Fu, Ph.D (Advanced Agrochem, 2023)
Aptamers are short, single-stranded DNA or RNA molecules that selectively bind to a target molecule. Aptamer-complement duplex (ACD) is often used to design molecular switches capable of producing a detectable signal or triggering a structural change upon aptamer binding to a target. However, such aptamer switch generally faces an increased dissociation constant (Kd) due to the energy barrier of the complementary duplex. We reported a competitive hybridization mechanism to modulate the binding affinity of an ACD to a target adenosine. Using the computation-guided design, we calculated the aptamer folding energy for the duplex length from 11-nt to 15-nt, and experimentally measured increased apparent Kd values resulted from these extended duplexes. Using a set of strands to compete with the ACD hybridization, it reduced the aptamer folding energy to facilitate aptamer switches with decreased apparent Kd values ranging from over 400 μM without a competing strand to ∼30 μM with a competing strand. This competitive aptamer switch was also found sensitive to single-nucleotide mutations of a competing strand. Our work provides an approach to modulate the binding affinity and the sensitivity of aptamer-complement duplexes, which could be useful in the nucleic acids-based sensing and nanomedicine.